Solar radiation explains litter degradation along alpine elevation gradients better than other climatic or edaphic parameters - Semeraro, Sarah; Kipf, Pascal; Le Bayon, Renée-Claire; Rasmann, Sergio (Frontiers in Microbiology, 2023)
Organic matter (OM) decomposition has been shown to vary across ecosystems, suggesting that variation in local ecological conditions influences this process. A better understating the ecological factors driving OM decomposition rates will allow to better predict the effect of ecosystem changes on the carbon cycle. While temperature and humidity have been put forward as the main drivers of OM decomposition, the concomitant role of other ecosystem properties, such as soil physicochemical properties, and local microbial communities, remains to be investigated within large-scale ecological gradients. To address this gap, we measured the decomposition of a standardized OM source - green tea and rooibos tea - across 24 sites spread within a fully factorial design including elevation and exposition, and across two distinct bioclimatic regions of the Swiss Alps. By analysing OM decomposition in respect to 19 climatic, edaphic or soil microbial activity-related variables, which strongly varied across sites, we identified solar radiation as the primary source of variation of both green and rooibos teabags decomposition rate. This study thus highlights the that while most variables, such as temperature or humidity, as well as soil microbial activity, do impact decomposition process, in combination with the measured pedo-climatic niche, solar radiation, very likely by means of indirect effects, best captures variation in OM degradation. For instance, high solar radiation might favour photodegradation, in turn speeding up the decomposition activity of the local microbial communities. Future work should thus disentangle the synergistic effects of the unique local bacterial and fungal community with the effect of solar radiation on OM decomposition across different habitats.